Initial Margin Policy and Stochastic Volatility in the Crude Oil Futures Market - Day, Theodore E.; Lewis, Craig M. (Review of Financial Studies, 1997)
This article examines the relationship between the volatility of the crude oil futures market and changes in initial margin requirements. To closely match changes in futures market volatility with the corresponding changes in margin requirements, we infer the volatility of the futures market from the prices of crude oil futures options contracts. Using a mean-reverting diffusion process for volatility, we show that changes in margin policy do not affect subsequent market volatility.